К вопросу о скифском этнокультурном компоненте на поселениях лесостепного Правобережья - Скорый, С. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummarySkoriy S. A. To the Question about Scythian Ethno-Cultural Component at Forest-Steppe Right-Bank SettlementThe paper deals with a type of dwelling investigated at the settlements of Scythian Period in Forest-Steppe of the Right-Bank of the Dnieper river. There were semi-dccpen earth-houses with a base, either round or circular, and a pit retined from central pole which could bear up a roof. It is possible to reconstruct the roof as similar to jurt or marquee. The date of such a dwellings is determined as a period from the end of VI century up to the V century B. C.The author considers that such dwellings are the material manifestation of the certain (probably the poorest) part of Nomadic Scythian tribes sedentarization as well as the reflection of their previous nomadic mode of life.